Chest X-rays for medical student: CXRs made easy - Clarke, C. Christopher (Wiley Blackwell, 2020)
Chest X-rays for Medical Students offers a fresh analytical approach to identifying chest abnormalities, helping medical students, junior doctors, and nurses understand the underlying physics and basic anatomical and pathological details of X-ray images of the chest. The authors provide a memorable framework for analysing and presenting chest radiographs, with each radiograph appearing twice in a side-by-side comparison, one as seen in a clinical setting and the second highlighting the pathology. This new second edition includes significant revisions, improved annotations of X-rays, expanded pathologies, and numerous additional high-quality images. A comprehensive one-stop guide to learning chest radiograph interpretation, this book: Aligns with the latest Royal College of Radiologists' Undergraduate Radiology Curriculum Offers guidance on how to formulate normal findings Features self-assessment tests, presentation exercises, and varied examples Includes sections on radiograph quality X-ray hazards and precautions Chest X-rays for Medical Students is an ideal study guide and clinical reference for any medical student, junior doctor, nurse or radiographer.